2009
DOI: 10.1097/wnn.0b013e3181b278d4
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in Everyday Life Activities and Sequence Disabilities in Tool use for Alzheimer Disease and Vascular Dementia

Abstract: Disturbances in everyday life activities of AD are associated with general cognitive impairment and sequence disabilities. By contrast, those of VaD may be based only on sequence disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Although some patients with dementia can perform routine activities and tasks adequately, the ability to solve more complex problems such as those found within work, social and domestic environments and in interpersonal relationships are usually affected 3 . Problem solving, measured by traditional neuropsychological tests or IADL scales 17 , 46 and decision making, evaluated by gambling tasks 47 , 48 are known to be affected in AD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Although some patients with dementia can perform routine activities and tasks adequately, the ability to solve more complex problems such as those found within work, social and domestic environments and in interpersonal relationships are usually affected 3 . Problem solving, measured by traditional neuropsychological tests or IADL scales 17 , 46 and decision making, evaluated by gambling tasks 47 , 48 are known to be affected in AD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Rapcsak, Croswell, and Rubens [32] and Okazaki, Kasai, Meguro, Yamaguchi, and Ishii [33] reported that IADL performance in individuals with AD was affected by executive function and apraxia. Moreover, Grossi, Becker, Smith, and Trojano [34] found that attentionallocation disorders arose in individuals with AD because of a reduction in their ability to perceive stimuli simultaneously.…”
Section: Study Limitations and Future Recommendationsmentioning
confidence: 99%
“…Action deficits in AD have been explored from two main perspectives. The first involves ideational apraxia, which refers to the loss of the ability to perform purposeful actions involving the operation of objects without impaired perception of the relevant tools, muscle weakness or abnormal motor skill of the fingers . Ideational apraxia includes sequence errors, such as skipping or changing the order of praxis stages.…”
Section: Introductionmentioning
confidence: 99%